Cognitive and affective evaluation in forming unique destination image among tourists visiting Malacca - Buyong, Edna; Rajiani, Ismi (Kogan Page, 2011)
Since Melaka is positioned as Historical City inaugurated by UNESCO in 2008, the study suggests unique image as a new component of image associations. A number of overseas tourists were selected as samples . Results showed that unique image was significantly constructed and affected by cognitive and affective evaluations. Cognitive evaluation was significantly affected by the types of information source, while affective evaluation was affected significantly by social psychological motivations. The research proves that Melaka has fulfilled the requirements to differentiate the city as a unique tourist destination. The positioning of Melaka as truly Malaysia and World heritage should be translated into the rational benefit of encountering unspoiled historical side and multi-racial living cultures. Positive unique image creation leads to intention to revisit and recommend others experiencing the world heritage and history of Melaka.